The expression of MMP‐1 and MMP‐9 is up‐regulated by smooth muscle cells after their cross‐talk with macrophages in high glucose conditions. Issue 9 (10th July 2018) - Macarie, Razvan Daniel; Vadana, Mihaela; Ciortan, Letitia; Tucureanu, Monica M.; Ciobanu, Andrea; Vinereanu, Dragos; Manduteanu, Ileana; Simionescu, Maya; Butoi, Elena
Abstract: Patients with diabetes mellitus have an increased risk of myocardial infarction and coronary artery disease‐related death, exhibiting highly vulnerable plaques. Many studies have highlighted the major role of macrophages (MAC) and smooth muscle cells (SMC) and the essential part of metalloproteases (MMPs) in atherosclerotic plaque vulnerability. We hypothesize that in diabetes, the interplay between MAC and SMC in high glucose conditions may modify the expression of MMPs involved in plaque vulnerability. The SMC‐MAC cross‐talk was achieved using trans‐well chambers, where human SMC were grown at the bottom and human MAC in the upper chamber in normal (NG) or high (HG) glucose concentration. After cross‐talk, the conditioned media and cells were isolated and investigated for the expression of MMPs, MCP‐1 and signalling molecules. We found that upon cross‐talk with MAC in HG, SMC exhibit: ( i ) augmented expression of MMP‐1 and MMP‐9; ( ii ) significant increase in the enzymatic activity of MMP‐9; ( iii ) higher levels of soluble MCP‐1 chemokine which is functionally active and involved in MMPs up‐regulation; ( iv ) activated PKCα signalling pathway which, together with NF‐kB are responsible for MMP‐1 and MMP‐9 up‐regulation, and ( v ) impaired function of collagen assembly. Taken together, our data indicate that MCP‐1 released by cell cross‐talk in diabetic conditions binds to CCR2 and triggers MMP‐1 and MMP‐9 over‐expression and activity, features that could explain the high vulnerability of atherosclerotic plaque found at diabetic patients.